First‐in‐Human Study of Bamlanivimab in a Randomized Trial of Hospitalized Patients With COVID‐19. Issue 6 (16th October 2021) - Chen, Peter; Datta, Gourab; Grace Li, Ying; Chien, Jenny; Price, Karen; Chigutsa, Emmanuel; Brown‐Augsburger, Patricia; Poorbaugh, Josh; Fill, Jeffrey; Benschop, Robert J.; Rouphael, Nadine; Kay, Ariel; et al.
Abstract : Therapeutics for patients hospitalized with coronavirus disease 2019 (COVID‐19) are urgently needed during the pandemic. Bamlanivimab is a potent neutralizing monoclonal antibody that blocks severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) attachment and entry into human cells, which could potentially lead to therapeutic benefit. J2W‐MC‐PYAA was a randomized, double‐blind, sponsor unblinded, placebo‐controlled, single ascending dose first‐in‐human trial (NCT04411628) in hospitalized patients with COVID‐19. A total of 24 patients received either placebo or a single dose of bamlanivimab (700 mg, 2, 800 mg, or 7, 000 mg). The primary objective was assessment of safety and tolerability, including adverse events and serious adverse events, with secondary objectives of pharmacokinetic (PK) and pharmacodynamic analyses. Treatment‐emergent adverse event (TEAE) rates were identical in the placebo and pooled bamlanivimab groups (66.7%). There were no apparent dose‐related increases in the number or severity of TEAEs. There were no serious adverse events or deaths during the study, and no discontinuations due to adverse events. PKs of bamlanivimab is linear and exposure increased proportionally with dose following single i.v. administration. The half‐life was ~ 17 days. These results demonstrate the favorable safety profile of bamlanivimab, and provided the initial critical evaluation of safety, tolerability, and PKs in support of the development of bamlanivimab in several ongoing clinical trials.